2008
DOI: 10.1088/0022-3727/41/14/144026
|View full text |Cite
|
Sign up to set email alerts
|

Application of an antenna excited high pressure microwave discharge to compact discharge lamps

Abstract: A novel type of high pressure microwave discharge has been investigated to feed the microwave power at the centre of the compact high pressure discharge lamps using the antenna effect. This method of microwave discharge is named as the antenna excited microwave discharge (AEMD). The 2.45 GHz microwave of around 50 W from the solid state microwave generator can sustain a stable plasma column in the small gap between a couple of antennas fitted on the compact lamp filled with discharge gases at a pressure higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Hussain [ 100 ] found the interaction of microwaves with iron led the iron’s temperature to rise up to 1100–1200 °C and even up to the melting point of iron. Kando et al [ 101 ] carried out some research on the excitation of microwave discharge by an antenna to produce high intensity microwave discharge and found a plasma column emitting strong radiation was produced in a small gap between a couple of antennas and the plasma column sometimes changed to a curved one with the increase of the incident microwave power. Chen et al [ 62 ] reported that audible and bright discharges accompanied by solvent decomposition and formation of considerable amounts of graphitized material were observed by adding metal particles (Mg, Zn, Cu) to liquid benzene under microwave irradiation.…”
Section: Effects Of Microwave-metal Interactionsmentioning
confidence: 99%
“…Hussain [ 100 ] found the interaction of microwaves with iron led the iron’s temperature to rise up to 1100–1200 °C and even up to the melting point of iron. Kando et al [ 101 ] carried out some research on the excitation of microwave discharge by an antenna to produce high intensity microwave discharge and found a plasma column emitting strong radiation was produced in a small gap between a couple of antennas and the plasma column sometimes changed to a curved one with the increase of the incident microwave power. Chen et al [ 62 ] reported that audible and bright discharges accompanied by solvent decomposition and formation of considerable amounts of graphitized material were observed by adding metal particles (Mg, Zn, Cu) to liquid benzene under microwave irradiation.…”
Section: Effects Of Microwave-metal Interactionsmentioning
confidence: 99%
“…During the startup of the plasma light source, the dielectric material inside the bulb changes into plasma from a low-pressure vacuum. Additionally, the relative permittivity ε p of the plasma is determined by the following formulas [22]:…”
Section: Design Of Control Flowmentioning
confidence: 99%
“…The work of Kando et al [6] shows an experimental setup to drive commercial mercury-containing HID lamps including electrodes by a 2.45-GHz signal. The setup consists of a solidstate amplifier, a rectangular waveguide, including a three-stub tuner and a moveable plunger, as well as the coaxial microwave launcher.…”
Section: Introductionmentioning
confidence: 99%